2020
DOI: 10.3949/ccjm.87a.ccc046
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of supplementation with ascorbic acid, zinc, vitamin D, or N-acetylcysteine for prevention or treatment of COVID-19?

Abstract: The statements and opinions expressed in COVID-19 Curbside Consults are based on experience and the available literature as of the date posted. While we try to regularly update this content, any offered recommendations cannot be substituted for the clinical judgment of clinicians caring for individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 10 publications
0
40
0
9
Order By: Relevance
“…NAC is approved by FDA under various formulations and is popular as a health supplement, this molecule having been proposed as a nutraceutical that might aid the control of RNA viruses including influenza and coronavirus. [64][65][66] Almost 60 years of experience in the prophylaxis and therapy of a variety of clinical conditions have established the safety of this drug, even at very high doses and for long-term treatments. Drug repurposing is the fastest strategy toward an effective and accessible treatment against COVID-19 before a vaccine is available, 67 and molecules working via multiple mechanisms of action, such as NAC, are more likely to be effective as compared with drugs having a single target.…”
Section: Discussionmentioning
confidence: 99%
“…NAC is approved by FDA under various formulations and is popular as a health supplement, this molecule having been proposed as a nutraceutical that might aid the control of RNA viruses including influenza and coronavirus. [64][65][66] Almost 60 years of experience in the prophylaxis and therapy of a variety of clinical conditions have established the safety of this drug, even at very high doses and for long-term treatments. Drug repurposing is the fastest strategy toward an effective and accessible treatment against COVID-19 before a vaccine is available, 67 and molecules working via multiple mechanisms of action, such as NAC, are more likely to be effective as compared with drugs having a single target.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a redox-sensitive transcription factor, which gets activated by oxidative stress (Das 2020 ). Blocking this pathway with antioxidants such as Vitamin A, Vitamin C, Glutathione, Vitamin E, Zinc and many others could have both prophylactic protection and also prevent progression of illness (Nwose and Bwititi 2020 ; Bauer et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed that serum and leukocyte levels of vitamin C is depleted during the acute stage of the infection [ 3 , 4 ]. Previous clinical trials found that supplementation with high dose of vitamin C decreased the severity and duration of respiratory viral infections [ 5 ]. Based on these findings, vitamin C might be used in management of COVID-19 as it might improve the immunological response against the novel coronavirus (SARS-CoV-2).…”
Section: Introductionmentioning
confidence: 99%
“…The pathological damage induced by SARS-CoV-2 infection is partially due to the direct viral virulence effect, but the main part is caused by massive host immune response and oxidative stress secondary to release of free radicals [ 5 ]. SARS-CoV-2 infection induces excessive release of proinflammatory cytokines, leading to cytokines storm, and increases production of reactive oxygen species which both cause significant lung damage which leads to subsequent development of adult respiratory distress syndrome (ARDS) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%